Clareamento parasitário de Plasmidium falciparum em resposta ao tratamento com artemisinina - Pinto, Raquel de Medeiros (2020)
In Brazil, Plasmodium falciparum resistance to several drugs, such as chloroquine, sulfadoxine- pyrimethamine, mefloquine, quinine and amodiaquine is reported. The monitoring of the sensitivity of Plasmodium to antimalarial drugs is of great importance for the therapeutic management and planning of malaria control policies. Currently, the World Health Organization (WHO) recommends Artemisinin-based combination therapy (ACT) as first-line for all cases of malaria in areas where P. falciparum predominates. In the present study, we analyzed a cohort of patients treated in a tertiary center of Manaus, with positive diagnosis of P. falciparum malaria by thick blood under treatment with artemisinin derivatives (artesunate, artesunate / mefloquine, artemether, artemether / mefloquine ) and followed over 35 days after treatment to evaluate the parasitic whitening profile. The variables evaluated were: date of service, gender, age, type of treatment, number of leukocytes, white blood cell count, sexual and asexual parasitaemia (D0) and day follow-up (D1-D7, D14, D21, D28 and D35). Survival analysis (AS) and logistic regression (LR) will be conducted to examine associations between parasitic and whitening treatment. For regression analysis, the outcome will be assessed parasitic whitening time in D3 and D4, while the survival analysis, the variable analyzed is the time to bleaching. Therefore the estimate of parasite clearance method provides a consistent, reliable and can be used to detect early signs of emerging resistance to artemisinin derivatives and other compounds used in treatment. The results could form the basis for future studies related to genetic polymorphisms associated with decreased of parasite clearance time in the Americas